Microfacies control on geomechanical properties of unconventional carbonate reservoirs: insights from a middle jurassic outcrop analogue in Saudi Arabia - Adamu Kimayim Gaduwang; Daniel Muñoz-López; Anas Muhammad Salisu; Bassam Tawabini; Khalid Al-Ramadan; Ardiansyah Koeshidayatullah (Journal of Petroleum Exploration and Production Technology)
Abstract The interplay between depositional and diagenetic processes controls the distribution of geomechanical properties in carbonate rocks. Understanding the distribution of geomechanical properties in rocks is crucial for analyzing the behavior of unconventional carbonate reservoirs during hydraulic fracturing. In Saudi Arabia, the exceptionally exposed Middle Jurassic Tuwaiq Mountain Formation (TMF) represents an important analog of its subsurface-equivalent unconventional reservoir. In this formation, petrographical, rock physical (Vp, Vs, Poisson’s Ratio, and Φ), and geomechanical (uniaxial compressive strength (UCS) and Dynamic Elastic Modulus (Ed)) analyses were integrated to examine how sedimentary microfacies controls the variation of geomechanical properties and thus, reservoir quality and heterogeneity in carbonate successions. Petrographic observations reveal that the TMF comprises three sedimentary microfacies including peloidal grainstone, bioclastic-peloidal packstone, and bioclastic wackestone. An integrated analysis indicates that these microfacies shows distinct petrophysical and geomechanical properties. The peloidal grainstone shows the highest average porosity of 15.4% and lowest average UCS value of 34Mpa, while the bioclastic wackestone exhibit the lowest average porosity of 2.8%, Poisson Ratio (0.26) and highest average UCS value of 148Mpa. Among the three microfacies, the bioclastic wackestone shows the highest average Vp value (5635.5 m/s) and Vs value (2935.25 m/s), and Young Modulus (Ed; up to 45 Gpa), suggesting a high brittleness and fracability. The findings reveal a strong correlation between depositional texture, sedimentary microfacies, and the rock physical and geomechanical properties of unconventional carbonate reservoirs. These insights can help in reservoir quality predictions and in the selection of sweet spots for hydraulic fracturing in complex carbonate sequences.